TEACHERS' STRATEGIES FOR INTRODUCING DEAF CHILDREN'S ORAL LANGUAGE - Fitriani, Dayang Astri; Saputri, Alifia Nur Elga; Az Zahrah, Sofie Aulia; Firdausia, Indah Salsabila; Kartika, Wilda Isna; Pertiwi, Adharina Dian (Universitas Al-Hikmah Indonesia, 2024)
This study discusses the strategies used by teachers in working on spoken language in deaf children at SLB Negeri Samarinda. The approach used is qualitative with descriptive methods, through direct observation and interviews with teachers as the main data source. Hearing loss is often an obstacle in communication skills, especially spoken language. The results show that teachers use various methods, such as lip reading, articulation exercises with the help of a mirror, and the use of visual media. In addition, a total communication approach combining sign language, spoken language and audio-visual technology is applied to help students understand and produce language more easily. Teachers also use games and educational songs to attract students' interest in learning. The role of parents is very important, especially through language practice at home. Active participation of parents in daily learning can accelerate the development of children's language skills. In addition, collaboration with therapists strengthens the learning process, as it is designed according to the specific needs of the child with the role of parents is very important, especially through language practice at home accelerates the development of language skills in conclusion, a combination of methods, family involvement, and an integrated approach can improve deaf children's spoken language skills, making them more confident and independent in their daily communication.